Low Serum Dehydroepiandrosterone and Dehydroepiandrosterone Sulfate Are Associated With Coronary Heart Disease in Men With Type 2 Diabetes Mellitus - Zhang, Xinxin; Xiao, Jinfeng; Liu, Tong; He, Qing; Cui, Jingqiu; Tang, Shaofang; Li, Xin; Liu, Ming (Frontiers in Endocrinology, 2022)
Abstract Aims: Sex hormones play an important role in the pathogenesis of cardiovascular disease (CVD). This cross-sectional study aimed to explore the associations of dehydroepiandrosterone (DHEA) and dehydroepiandrosterone sulfate (DHEAS) with coronary heart disease (CHD) and stroke in middle-aged and elderly patients with type 2 diabetes mellitus (T2DM). Materials and methods: A total of 995 patients with T2DM were included in the study analysis. Serum levels of DHEA and DHEAS were quantified using liquid chromatography-tandem mass spectrometry. Binary logistic regression analyses were performed to assess the associations of DHEA and DHEAS with CHD and stroke. Receiver operating characteristic (ROC) curve analysis was performed to determine the optimal DHEA and DHEAS cut-off values for the detection of CHD in men with T2DM. Results: In men with T2DM, after adjustment for potential confounders in model 3, the risk of CHD decreased with increasing serum DHEA level (Odds ratio [OR], 0.38; quartile 4 vs. quartile 1; 95% confidence interval [CI], 0.16–0.90; P = 0.037 for trend). Consistently, when considered as a continuous variable, this association remained significant in the fully adjusted model (OR, 0.59; 95% CI, 0.40–0.87; P < 0.05). When taken as a continuous variable in model 3, serum DHEAS level was also inversely related to the risk of CHD among men (OR, 0.56; 95% CI, 0.38–0.82; P < 0.05). Similarly, this relationship remained statistically significant when DHEAS was categorized into quartiles (OR, 0.27; quartile 4 vs. quartile 1; 95% CI, 0.11–0.67; P = 0.018 for trend). ROC curve analyses revealed that the optimal cut-off values were 6.43 nmol/L for DHEA and 3.54 μmol/L for DHEAS to detect CHD in men with T2DM. In contrast, no significant associations were found between DHEA and DHEAS on the one side and stroke on the other in men and women with T2DM (all P > 0.05). Conclusions: Serum DHEA and DHEAS were significantly and negatively associated with CHD in middle-aged and elderly men with T2DM. This study suggests a potential role of DHEA and DHEAS in CHD pathogenesis.